Credit market competition and the nature of firms - Nicola Cetorelli (Federal Reserve Bank of New York, 2009)
Empirical studies show that competition in the credit markets has important effects on the entry and growth of firms in nonfinancial industries. This paper explores the hypothesis that the availability of credit at the time of a firm's founding has a profound effect on that firm's nature. I conjecture that in times when financial capital is difficult to obtain, firms will need to be built as relatively solid organizations. However, in an environment of easily available financial capital, firms can be constituted with an intrinsically weaker structure. To test this conjecture, I use confidential data from the U.S. Census Bureau on the entire universe of business establishments in existence over a thirty-year period; I follow the life cycles of those same establishments through a period of regulatory reform during which U.S. states were allowed to remove barriers to entry in the banking industry, a development that resulted in significantly improved credit competition. The evidence confirms my conjecture. Firms constituted in post-reform years are intrinsically frailer than those founded in a more financially constrained environment, while firms of pre-reform vintage do not seem to adapt their nature to an easier credit environment. Credit market competition does lead to more entry and growth of firms, but also to complex dynamics experienced by the population of business organizations.
Keywords: L20; G20; 330; Firm dynamics; credit reform; imprinting